Where She Always Was - Lindsay, Frannie (Utah State University, University Libraries, 2004)
May Swenson Poetry Award Volume 8, with foreward by J. D. McClatchy. In his Foreword, McClatchy speaks of the musical qualities of Lindsay's work: ""It is impossible, reading her poems, not to hear a musical hand at work. This is not just a matter of delicacy or virtuosity. It is also a matter of knowing how to phrase a line... Lindsay moves from detail to trope with utter poise, with an intuitive sense of what to sustain or emphasize. Her language is crisp. I can pick a stanza at random... and praise its plosive energy, its modulated vowels, its variety and elan... Where She Always Was allows us . . . the rare gratification of watching a poet-wonderfully accomplished, quietly persuasive-look back on a lifetime's worth of emotions and calculate their bearing on the present. In her craft is the truth.""